2006
DOI: 10.1002/bip.20563
|View full text |Cite
|
Sign up to set email alerts
|

Influence of point mutations on the flexibility of cytochrome b5: Molecular dynamics simulations of holoproteins

Abstract: Two membrane-bound isoforms of cytochrome b5 have been identified in mammals, one associated with the outer mitochondrial membrane (OM b5) and the other with the endoplasmic reticulum (microsomal, or Mc b5). The soluble heme binding domains of OM and Mc b5 have highly similar three-dimensional structures but differ significantly in physical properties, with OM b5 exhibiting higher stability due to stronger heme association. In this study, we present results of 8.5-ns length molecular dynamics simulations for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The Δν = 646 and 723 cm −1 peaks are characteristic peaks for lipid according to Drescher 40 , while the Δν = 1460 and 1712 cm −1 peaks result from vibrational modes in proteins. In addition, i 32 also increased significantly at peaks Δν = 951, 1089, 1124, 1247, 1330 and 1377 cm −1 , which represent the structure change of membrane lipids and proteins 28,3033,41 . However, i159932 (≈ 2.6) stayed almost the same as i159924, which indicated that the peak at Δν = 1599 cm −1 is the most appropriate SERS peak to characterize the ring stage iRBCs.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The Δν = 646 and 723 cm −1 peaks are characteristic peaks for lipid according to Drescher 40 , while the Δν = 1460 and 1712 cm −1 peaks result from vibrational modes in proteins. In addition, i 32 also increased significantly at peaks Δν = 951, 1089, 1124, 1247, 1330 and 1377 cm −1 , which represent the structure change of membrane lipids and proteins 28,3033,41 . However, i159932 (≈ 2.6) stayed almost the same as i159924, which indicated that the peak at Δν = 1599 cm −1 is the most appropriate SERS peak to characterize the ring stage iRBCs.…”
Section: Resultsmentioning
confidence: 94%
“…1 are from these major membrane components, and the detailed peak assignments are listed in Table 1. The characteristic peaks at Δν = 421, 519, 957, 1064, 1124, 1330 and 1379 cm −1 are assigned to the vibrational mode of lipids 2831 , peaks at Δν = 749, 1258, 1552 and 1618 cm −1 represent vibrational modes of membrane proteins 30,32,33 , and peaks at Δν = 840 and 898 cm −1 could be assigned to saccharide bands 34 .…”
Section: Resultsmentioning
confidence: 99%
“…showed that an open-closed cleft transition occurs in this region for bovine and other cyt b 5 species [24,26,28].…”
Section: Resultsmentioning
confidence: 96%
“…To date, plenty of theoretical studies have been performed for cyt b 5 [24][25][26][27][28][29][30][31][32], cyt b 562 [33][34][35][36], and cyt c [37][38][39]; these studies have aimed to gain structural insights, as well as to elucidate the mechanisms of holoprotein maturation. Using molecular modeling in combination with MD simulations, we recently studied the structural consequences of introducing a histidine tag, the (His) 6 tag, to the N-terminus of bovine Mc cyt b 5 [32].…”
Section: Introductionmentioning
confidence: 99%
“…The potentials of DNA were increasingly recognized especially in the applications of biosensors, catalytic membranes, absorbing membranes and support for catalysts [1,2]. However, DNA is unstable in aqueous solution, resulting in denaturation of nucleic acid structure after 1 month of storage at ambient temperature [3].…”
Section: Rizana Et Al: Studies Of Interaction Between Tetrabutylammonmentioning
confidence: 99%